Women, Sexuality and Health - (:unkn) unknown (Sistren Theatre Collective, Kingston Jamaica, 2018)
Sistren is published three times per year by the Sistren Theatre Collective as part of its on-going efforts to highlight issues of concern to women in the society. Sistren is a non-profit making collective of women. Other activities include theatre, workshops using Drama-in-Education methodology and research.
Keywords: Health education of women; Women—Sexual behavior; Women -- Caribbean Area